Social participation and depression among resettled Syrian refugees: examining a moderated mediation of social support and bonding or bridging social capital - Johnson-Singh, Charisse M.; Sengoelge, Mathilde; Engström, Karin; Saboonchi, Fredrik (Frontiers in Psychology, 2024)
Characteristics of social networks are among the factors influencing refugee mental health after resettlement. This study aims to model the mediatory role of social support and the moderating effects of social capital in the association between social participation and depressive symptoms in a cohort of 464 Syrian refugees resettled in Sweden. Multigroup structural equation modelling was used to investigate these relationships between two social capital groups—bonding networks (social participation with coethnic individuals) and bridging networks (social participation with Swedes). The results showed that frequent social participation, compared to rare or no participation, was significantly associated with lower depressive symptoms, regardless of whether participation included a broad or limited range of activities. Bonding networks amplified the effect of social participation on depressive symptoms via increased social support, resulting in those with bonding networks showing an overall twofold decrease in depressive symptoms compared to those with bridging networks. While both bonding and bridging networks are beneficial to mental health, the findings of this study confirm that having access to coethnic networks in the early stages of resettlement provides a particularly important source of social support.